Prmt1-mediated methylation regulates Ncoa4 stability to transactivate Adamts genes and promote bone extracellular matrix degradation in chronic hematogenous osteomyelitis - Xun Chen; Ning Duan; Wentao Zhang; Tao Song; Fei Cong (Biology Direct)
Abstract Background Protein arginine methyltransferases (Prmts) are essential regulators of various biological processes and have been implicated in the pathogenesis of numerous diseases. However, their role in osteomyelitis remains poorly understood. Methods A mouse model of chronic hematogenous osteomyelitis (CHOM) was established by intravenous inoculation with Staphylococcus aureus (S. aureus). Gene and protein expression levels were quantified using RT-qPCR and immunoblot analysis, respectively. Protein interactions were determined via immunoprecipitation and co-immunoprecipitation assays. In vitro and in vivo assays were employed to evaluate protein methylation and ubiquitination. Bone destruction was assessed through histological staining. Results Among 9 Prmt members, Prmt1 was the only one significantly upregulated in osteomyelitis-affected mice. Our findings revealed that the inflammatory microenvironment specifically upregulated Prmt1 expression in osteoblasts and osteocytes, which facilitated its interaction with the transcriptional activator Ncoa4 (nuclear receptor coactivator 4) and mediated Ncoa4 arginine methylation, thereby enhancing Ncoa4 protein stability. Methylated Ncoa4 formed a transcriptional complex with the histone acetyltransferase Cbp (CREB-binding protein) and transcription factor Ap1 (Activator protein 1), driving the expression of four Adamts genes (Adamts3/8/12/14) that promoted extracellular matrix (ECM) degradation in osteoblasts and osteocytes. In contrast, depletion or pharmacological inhibition of Prmt1 prevented Ncoa4 methylation upon stimulation with pro-inflammatory cytokines, leading to Ncoa4 ubiquitination by Rnf8 (Ring finger protein 8) E3 ligase and subsequent proteasomal degradation, eventually leading to downregulation of Adamts expression. Importantly, treatment with Prmt1 inhibitors TCE-5003 and MS023 significantly mitigated bone ECM degradation and prevented osteomyelitis progression in S. aureus-infected mice. Conclusion These findings identify Prmt1 as a pivotal regulator of bone ECM degradation in osteomyelitis through stabilization of Ncoa4 and highlight Prmt1 as a promising therapeutic target for osteomyelitis treatment.